Youth Labor Markets in the United States: Shopping Around vs. Staying Put - Neumark, David (The Review of Economics and Statistics, 2002)
The need for school-to-work programs or other means of increasing early job market stability is predicated on the view that the “chaotic” nature of youth labor markets in the United States is costly because workers drift from one job to another without developing skills, behavior, or other characteristics that in turn lead to higher adult earnings. However, there is also ample evidence that workers receive positive returns to job shopping. This paper asks whether youths in unstable jobs early in their careers suffer adverse labor market consequences as adults. Its specific contribution is to account for the endogenous determination of early job stability and adult wages as outcomes of a job search/job shopping process. Labor market conditions in the early years in the labor market are used as instrumental variables for the job stability experienced during those years. The instrumental variables estimates generally point to substantial positive effects of early job stability on adult wages, in contrast to OLS estimates, which indicate little or no relationship.